Mitochondrion at the Crossroad Between Nutrients and Epigenome - Taormina, Giusi; Russo, Antonio; Latteri, Mario A.; Mirisola, Mario G. (Frontiers in Endocrinology, 2019)
Epigenetic profile can be considered the link between the regulation of nuclear gene expression and the environment. The most important factors capable to significantly affect the cellular environment are the amount and quality of the available nutrients. The role of the mitochondria is clearly critical into this process since they convert nutrients into usable energy. Carbohydrate and fats are in fact converted into ATP, acetyl-CoA, SAM, and NADH. These high energy substrate are in turn, as briefly described, capable to drive the epigenetic profile. Interestingly, nutritional intervention capable to reduce the calorie level or significantly impair the normal Acetyl-CoA production or the SAM-SAH ratio can impact chromatin methylation and histone modification, compacting the chromatin, and reducing gene expression, growth and reproduction.